The Politics of Location, British Council Conference on Places and Spaces, 8.-12.09.2003., Delphi, Greece - Gjurgjan, Ljiljana Ina (2003)
The lecture looks into the question of the respnsibility of the critic and concludes that . postcolonial criticism, though polemical in its rhetoric, has lost its social edge, and become (with its academic courses and conferences) an industry in its own right. Therefore the question is: to what extend postcolonial criticism has contributed to a frame of mind that would recognize market economy and multinational companies as the best national interest even in those cultures that till recently might have been described as autonomous, even if, by the Western standards, backwards.